The evolution of nostalgia in Britain 1979–2019 - Heath, A; Richards, L; Jungblut, J (Wiley, 2022)
This paper uses the British Election Surveys from 1979 to 2019, together with the 2016–2019 CSI Brexit online panel, to explore how nostalgia has changed over time. Our interpretation of the data is that there was a shift in the content of nostalgia from regret about the decline of traditional ways of life and family values toward regret over the rise of inequality and the emergence of social media. At the same time, we find continuity in the kinds of people who are likely to feel nostalgic: they tend to be members of older generations and to be less well educated (which we take as a proxy for being “left behind” culturally and economically). However, we also find that, on the items for which we have comparable time series—on immigration, same-sex relations, ethnic equality, and gender equality—both age and educational level have reducing explanatory power over time. In contrast, for these items, there is a trend toward greater politicization and an increased influence of an English national identity. Political divisions show increasing explanatory power as sociodemographic divisions decline.